Outcome measures in the management of gluteal tendinopathy: a systematic review of their measurement properties. Issue 15 (8th April 2022) - Nasser, Anthony M; Fearon, Angela M; Grimaldi, Alison; Vicenzino, Bill; Mellor, Rebecca; Spencer, Trevor; Semciw, Adam Ivan
Abstract : Objective: Evaluate properties of outcome measures for gluteal tendinopathy. Design: Multistage scoping/systematic review. Data sources: Cochrane, PubMed, Embase, Scopus, Web of Science, PEDro, CINAHL, SPORTDISCUS were searched (December 2021) to identify measures used to evaluate gluteal tendinopathy. Measures were mapped to the core health domains for tendinopathy. Medline, CINAHL, Embase and PubMed were searched (December 2021) for studies evaluating measurement properties of gluteal tendinopathy outcome measures captured in the initial search. Both reviews included studies that evaluated a treatment in participants with gluteal tendinopathy, diagnosed by a professional. Consensus-based-Standards for the Selection of Health Instruments methodology were followed—including bias assessment and synthesis of findings. Results: Six studies reported on the Victorian Institute of Sport Assessment—Gluteal Tendinopathy (VISA-G). One study reported on the Hip Outcome Score (HOS)—activities of daily living (ADL) and Sport. The VISA-G had moderate-quality evidence of sufficient construct validity (known group) and responsiveness (pre–post intervention), low-quality evidence of sufficient reliability, measurement error, comprehensibility and insufficient construct validity (convergent), and very low-quality evidence of sufficient comprehensiveness, relevance and responsiveness (comparison with other outcome measures). Both the HOS(ADL) and HOS(Sport) had very low-quality evidence of sufficient reliability, relevance and insufficient construct validity and comprehensiveness. The HOS(ADL) had very low-quality evidence of sufficient comprehensibility and insufficient measurement error. The HOS(Sport) had very low quality evidence of inconsistent comprehensibility and sufficient measurement error. Conclusion: Rigorously validated outcome measures for gluteal tendinopathy are lacking. The VISA-G is the preferred available option to capture the disability associated with gluteal tendinopathy.